URGENSI KECERDASAN EMOSI TERHADAP AGRESIVITAS PADA ANGGOTA POLISI - Ayu Aulia Rahmayanti; Sabrina Zahwa, Siti Fatimah Azzahraa, Tugimin Supriyadi, Tyo Hendryan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study examines the urgency of emotional intelligence on aggressiveness in police officers in the Indonesian police force. Aggressiveness in the form of physical and verbal can be caused by several internal factors and external factors. Emotional intelligence is an individual's ability to regulate and manage emotions that are believed to influence individual aggressive behavior. This research method uses a case study method and literature study to examine the urgency between emotional intelligence and aggressiveness in police officers. The results of this study indicate that emotional intelligence is very important for every police officer to control emotions or feelings, be calm, persuasive and able to provide the best service to the community as expected by the community.